2021
DOI: 10.1001/jamacardio.2021.3055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Treatment With Progression of Coronary Atherosclerotic Plaque Composition

Abstract: IMPORTANCEThe density of atherosclerotic plaque forms the basis for categorizing calcified and noncalcified morphology of plaques.OBJECTIVE To assess whether alterations in plaque across a range of density measurements provide a more detailed understanding of atherosclerotic disease progression. DESIGN, SETTING, AND PARTICIPANTSThis cohort study enrolled 857 patients who underwent serial coronary computed tomography angiography 2 or more years apart and had quantitative measurements of coronary plaques through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 25 publications
5
49
0
1
Order By: Relevance
“…The first reports concerning cases of myocarditis temporally linked to the vaccination with the mRNA vaccines from Comirnaty and Spikevax came from the Israeli Ministry of Health and the U.S. Department of Defense [ 4 ]. To date, there are single case reports and case series published describing myocarditis following vaccination with Comirnaty or Spikevax with rather mild courses [ 2 , 4 , 9 , 17 , 30 , 37 , 40 43 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first reports concerning cases of myocarditis temporally linked to the vaccination with the mRNA vaccines from Comirnaty and Spikevax came from the Israeli Ministry of Health and the U.S. Department of Defense [ 4 ]. To date, there are single case reports and case series published describing myocarditis following vaccination with Comirnaty or Spikevax with rather mild courses [ 2 , 4 , 9 , 17 , 30 , 37 , 40 43 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to pro-inflammatory cytokines may reduce the risk of adverse cardiovascular events, particularly in patients with CRP <2 mg/L, and anti-inflammatory therapy may be indicated at the start of dialysis, but more clinical findings are needed to support this ( Dhorepatil et al, 2019 ). A 2021 study of a population with coronary heart disease using statins for more than 2 years showed that statins caused a gradual shift to higher density calcification of coronary atherosclerotic plaques while attenuating the progression of coronary atherosclerotic plaque size, but the explanation for the acceleration of coronary atherosclerotic plaque calcification by statins remains controversial ( van Rosendael et al, 2021 ).…”
Section: Oxidative Stress Mechanisms Parallel To Inflammationmentioning
confidence: 99%
“…In the absence of contraindications, all patients with obstructive CAD on CCTA received optimal medical treatment, including statins, as recommended by current guidelines ( 2 ). Although a recent study has emphasized the effects of statins on plaque composition ( 35 ), the detailed medical regimen was not prospectively collected and this question was beyond the scope of the study. Symptoms were assessed by the sole presence of symptomatic angina or dyspnea on exertion without standardized classification.…”
Section: Discussionmentioning
confidence: 99%